Transtorno da personalidade Borderline, suas nuances e o engajamento terapêutico - Adami, Alessandro (2020)
The borderline personality disorder causes significant psychological and social malaise to whom affected, they have difficulty in establishing relationships, interpersonal bonds and organizing their own lives. Those who have this disorder, have diverse symptoms: unstable mood, impulsiveness, self-destruction, among others. Our aim is to know the therapeutic process used in patients with borderline personality disorder, from the perspective of health professionals, an exploratory descriptive study of qualitative approach was carried out in the city of Passo Fundo, Rio Grande do Sul, with three psychiatrists and four psychologists in their professional activities. In order to recruit them, the research was disseminated in the researcher's circle of coexistence and the snowball technique was chosen. To collect data, semi-structured interviews of variable duration were carried out, with a guiding script having as key point, the understanding of the interviewee about the therapeutic process of the patient with borderline personality disorder and the repercussion in the life of those patients. The technique of thematic analysis was used in the treatment of the data. The project was approved by the Research Ethics Committee of Passo Fundo University. The result points out that the participants use psychoanalysis and cognitive-behavioral psychology, also considering pharmacology as more effective intervention techniques in the treatment, observing that the therapeutic process with these patients implies a different setting, focused on the relational, environmental and binding issue. This condition does not allow the use of a specific technique, but rather a combination of different therapeutic strategies, based on psychodynamics, limits and organization of the patient's behavior, observing the fulfillment of their needs through an empathic and binding welcome, being aware of their suffering and way of being. Due to the psychodynamic conditions, the patients present difficulties in the therapeutic engagement, as well as constantly putting themselves at risk, thus pointing out the need for a psychotherapy that can create something new, a condition that points to the need to train professionals with a sensitive eye on the patient and not only the technique.